2013
DOI: 10.7448/ias.16.4.18751
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of HIV among female sex workers, their clients, men who have sex with men and people who inject drugs in West and Central Africa

Abstract: Introduction The West and Central Africa (WCA) sub-region is the most populous region of sub-Saharan Africa (SSA), with an estimated population of 356 million living in 24 countries. The HIV epidemic in WCA appears to have distinct dynamics compared to the rest of SSA, being more concentrated among key populations such as female sex workers (FSWs), men who have sex with men (MSM), people who inject drugs (PWID) and clients of FSWs. To explore the epidemiology of HIV in the region, a systematic review of HIV li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
80
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(85 citation statements)
references
References 104 publications
2
80
0
1
Order By: Relevance
“…14-16 Likewise, with respect to Togo, the same review identified only 1 study has investigated HIV among FSW but also document a high prevalence of HIV at 36.2% (95% CI: 33.6 to 38.8) and 7.9% prevalence among clients (95% CI: 6.6 to 8.0), demonstrating concentration of infection among these key populations. 14,17 Analysis of factors associated with or predicting HIV infection among FSWs and clients has predominantly focused on the individual level, identifying inconsistent condom use, alcohol or other substance use, STI, and number of sexual partners/clients as key correlates of HIV infection. 12,[18][19][20] More recently, however, emerging research has demonstrated the impact of structural factors, such as criminalizing policies, workplace environment, violence, and stigma, on the HIV epidemic among FSWs.…”
Section: Introductionmentioning
confidence: 99%
“…14-16 Likewise, with respect to Togo, the same review identified only 1 study has investigated HIV among FSW but also document a high prevalence of HIV at 36.2% (95% CI: 33.6 to 38.8) and 7.9% prevalence among clients (95% CI: 6.6 to 8.0), demonstrating concentration of infection among these key populations. 14,17 Analysis of factors associated with or predicting HIV infection among FSWs and clients has predominantly focused on the individual level, identifying inconsistent condom use, alcohol or other substance use, STI, and number of sexual partners/clients as key correlates of HIV infection. 12,[18][19][20] More recently, however, emerging research has demonstrated the impact of structural factors, such as criminalizing policies, workplace environment, violence, and stigma, on the HIV epidemic among FSWs.…”
Section: Introductionmentioning
confidence: 99%
“…The HIV epidemic in the general population of West and Central Africa has generally not reached the same proportions as that in East and Southern Africa, and HIV infection here appears to be more similar to the HIV epidemics in Europe, Asia and the USA, with high HIV prevalence among particular at-risk groups, including MSM, and relatively low HIV prevalence among the general population [3]. In Nigeria, for example, Vu, Adebajo et al [22] report HIV prevalence rates ranging from 11.3 to 34.9 % among MSM in three cities, and note that these rates are 4-10 times higher than HIV prevalence in the general population.…”
Section: The Epidemiology Of Hiv In Msm In Ssamentioning
confidence: 76%
“…In contrast to the generalised epidemics occurring in Southern and Eastern Africa, HIV in West and Central Africa appears to be much more concentrated within high-risk groups such as men who have sex with men (MSM), commercial sex workers (CSW) and injectingdrug users (IDU) [1][2][3]. However, in spite of these differences in the overall characteristics of the epidemic, HIV prevalence is disproportionately high among MSM populations throughout SSA, and recent research has shown that the factors driving HIV risk among MSM in SSA are frequently similar across the many countries in SSA.…”
Section: Introductionmentioning
confidence: 98%
“…In West and Central Africa specifically, the pooled HIV prevalence among FSW in the region is estimated to be 34.9%. 5 Within the region of West Africa, the prevalence among reproductive age adults in Côte d’Ivoire has been estimated to be approximately 3.5%, with the burden among FSW observed to be many times higher. 5,6 …”
Section: Introductionmentioning
confidence: 99%